2009
DOI: 10.1161/strokeaha.109.564765
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging, White Matter Lesions, the Corpus Callosum, and Gait in the Elderly

Abstract: Background and Purpose-Gait impairment is common in the elderly, especially those with stroke and white matter hyperintensities on conventional brain MRI. Diffusion tensor imaging (DTI) is more sensitive to white matter damage than conventional MRI. The relationship between DTI measures and gait has not been previously evaluated. Our purpose was to investigate the relationship between the integrity of white matter in the corpus callosum as determined by DTI and quantitative measures of gait in the elderly. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
79
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 28 publications
10
79
1
1
Order By: Relevance
“…There existed a significant association between white matter lesion load and severity of DTI and MTR measures in the normalappearing white matter with the microstructural changes in normal brain tissue being more closely related to the patients' clinical presentation than the volume of visible white matter abnormalities [9,32,52,61,69,70,74,92,93]. These observations clearly indicate that age-related small vessel disease of the brain is a diffuse process affecting the entire brain and that white matter lesions are probably only the tip of the iceberg.…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 81%
“…There existed a significant association between white matter lesion load and severity of DTI and MTR measures in the normalappearing white matter with the microstructural changes in normal brain tissue being more closely related to the patients' clinical presentation than the volume of visible white matter abnormalities [9,32,52,61,69,70,74,92,93]. These observations clearly indicate that age-related small vessel disease of the brain is a diffuse process affecting the entire brain and that white matter lesions are probably only the tip of the iceberg.…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 81%
“…The corpus callosum is a dense bundle of neural fibres that connects the two cerebral hemispheres of the brain. Previous studies have reported a critical link between white matter integrity in the corpus callosum and both cognitive and mobility measures (e.g., Bhadelia et al, 2009;Frederiksen et al, 2011;Moscufo et al, 2011;Moscufo et al, 2012;Ryberg et al, 2011;Ryberg et al, 2007). Of particular relevance, atrophy in the splenium -a posterior region of the corpus callosum -appears to be most associated with reduced general mobility (e.g., Frederiksen et al, 2011;Moscufo et al, 2011;Moscufo et al, 2012) as measured by the Short Physical Performance Battery (SPPB) (Guralnik, Ferrucci, Simonsick, Salive, & Wallace, 1995).…”
Section: Primary Findingmentioning
confidence: 99%
“…14,19,24 The only MTR study in healthy, older adults described a relationship between wholebrain MTR and gait velocity. 23 The authors of this investigation quantified MTR changes globally by using histogram-based metrics.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by 2 DTI studies that reported the higher mean diffusivity and lower fractional anisotropy in the genu of the corpus callosum to be correlated with poorer gait performance independent of visible WMHs. 14,19 Complementary information on microstructural brain tissue alterations may come from magnetization transfer imaging (MTI). Other than DTI, which offers information on brain tissue organization, 20 MTI offers information on tissue composition.…”
mentioning
confidence: 99%